Financial Planning Aspects in the Era of Digital at NGO Permai Penang - HIDAYAH, Nurul; UTAMI, Fransisca L; ALI, Anees Janee (Indonesia Strategic Sustainability, 2024)
Pertubuhan Masyarakat Indonesia (PERMAI) Penang has been an NGO registered with the Malaysian Organization Registration (Register of Society/ROS) since 2019, with the number 006-07-04022019. PERMAI Penang operates in the social and educational sectors. PERMAI Penang is an abbreviation of the Indonesian Community Organization in Pulau Pinang, Malaysia. An NGO or non-governmental, non-political organization operating in the social, educational and cultural fields. PERMAI members or experts are Indonesian people living in Malaysia, including workers, expatriates, lecturers, teachers, students and scholars. This NGO aims to educate the Indonesian people and ensure Indonesian children in Malaysia receive an education. In order to become an incubator, they need to have unique skills and abilities so that they can get jobs in positions and salaries that are higher or at least equal to other nations. The community service team from UMB had been holding training activities with objective items to address understanding financial planning. In the era of new-age technology with which technology has penetrated every inch of people's everyday lives, even how we plan and operate our investments and financial planning. Understanding and embracing the modern financial planning aspects in the new digital economy is wiser. The results of this PKM will provide scientific insight with presentations regarding financial management in business.